Ecosystem Services Valuation as an Opportunity for Inquiry Learning - Taylor, Zachary P.; Bennett, Drew E. (Journal of Geoscience Education, 2016)
Teaching ecosystem services provides an ideal opportunity to use inquiry-based learning to help students make connections between ecological, geological, and social systems. The idea of ecosystem services, or the benefits nature provides to society, has emerged as a key concept in a host of environmental fields and is just beginning to gain attention within the geosciences. Although the concept has the potential to positively affect policy decisions by quantifying the economic value of ecosystem services, it has been criticized for commodifying nature and having limited engagement with geoscience perspectives. To teach ecosystem services to the next generation of geoscientists, we developed two variations of an inquiry-based learning exercise in which students used the ecosystem services approach to assign a monetary value to eight different ecosystem services generated by four ecosystems. One version of the exercise had students make these valuations in the field, whereas one was completed solely in the classroom. In both cases, the students scored significantly better on a postexercise assessment, demonstrated a deeper understanding of the ecosystem services approach, and reported that the exercise was preferable to a traditional lecture. Our data and observations also suggest that this exercise offers a great deal of flexibility and can be used in many learning environments. Geoscientists should be especially interested in integrating the concept of ecosystem services into their courses so that the next generation of geoscientists is well positioned to contribute to the interdisciplinary field of ecosystem services.
Keywords: ecosystem services; environmental science; inquiry learning; pedagogy